Strategi Pembinaan Religiusitas Anak dalam Keluarga - Safriadi Safriadi; Ismail Darimi; Irman Siswanto (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2015)
The cultivation of religious values according to Islam is to implement religious teachings or Islam as a whole. Every Muslim in thinking, acting or acting is commanded to accept Islam. In conducting any economic, social, political or activity activities a Muslim is enjoined to do so in order to worship and obey Allah Almighty. Thus the formation of religiosity becomes very important for life, especially for children in the family as a young generation or the next generation of the nation.